2020
DOI: 10.1093/pm/pnaa388
|View full text |Cite
|
Sign up to set email alerts
|

Additive Analgesic Effect of Transcranial Direct Current Stimulation Together with Mirror Therapy for the Treatment of Phantom Pain

Abstract: Objective Current analgesic treatments for phantom pain are not optimal. One well-accepted yet limited nonpharmacological option is mirror therapy, which is thought to counterbalance abnormal plasticity. Transcranial direct current stimulation (tDCS) is an emerging approach believed to affect the membrane potential and activity threshold of cortical neurons. tDCS analgesic effectiveness, however, is mild and short, rendering it a noneffective stand-alone treatment. This study aimed to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 39 publications
0
47
0
1
Order By: Relevance
“…All the studies used a combination of tDCS and another non-pharmacological neuromodulatory approach. In all studies, the tDCS intensity was set to 2mA, except for Segal et al (12), which used 1.5 mA. In all the studies, the tDCS duration was 20 min, except in 16), in which posttreatment pain intensity was measured at the end of treatment (and not 1 month later) because follow-up data at 1 month were unavailable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All the studies used a combination of tDCS and another non-pharmacological neuromodulatory approach. In all studies, the tDCS intensity was set to 2mA, except for Segal et al (12), which used 1.5 mA. In all the studies, the tDCS duration was 20 min, except in 16), in which posttreatment pain intensity was measured at the end of treatment (and not 1 month later) because follow-up data at 1 month were unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…The other neuromodulatory approaches that were combined with the tDCS could be grouped into 4 categories: The first category includes mirror therapy (12)(13)(14)(15), visual illusion (16- 18,22) and motor graded imagery (24). These three interventions…”
Section: Combining Tdcs With Other Non-pharmacological Neuromodulator...mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly a recent RCT combining transcranial direct current stimulation (tDCS) with mirror therapy showed that it resulted in higher pain reduction than mirror therapy alone in phantom limb pain [33]. Validation of the best combination has still to be investigated.…”
Section: Neurostimulation Multimodal Approaches and Psychotherapymentioning
confidence: 99%